Faktor-Faktor Yang Mempengaruhi Struktur Modal Dan Kebijakan Dividen Yang Terdaftar Di Jakarta Islamic Index (JII) Periode 2010-2014 - Yulianti Dwi Puji; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of this research is to determine the direct effects of factors that caused capital structure and dividend policy. The approach research used are quantitative with analytical techniques PLS (Partial Least Square). The approach is a quantitative approach using analytical techniques PLS (Partial Least Square). Data collection using purposive sampling method and examines a sample of 12 company that that have fixed sign position in the JII during 2010-2014.The results of this research show that in profitability has positive significant effect on capital structure which is indicated with t-statistic is 2,409. Liquidity has negatif not significant on capital structure which is indicated with t-statistic 1,678. Capital structure has negatif significant effect on dividend policy which is indicated with t-statistic 3,568.